PENGARUH KUALITAS INFORMASI DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DIMEDIASI OLEH KEPERCAYAAN KONSUMEN PADA PENGGUNA APLIKASI E-COMMERCE DI KOTA BANDA ACEH - T. M. Murfid Maulana; Nasir Nasir (Departemen Manajemen, 2021)
This study aims to examine the effect quality of information and perceived ease of use on Online purchasing decisions mediated by consumer confidence in e-commerce application users in the city of Banda Aceh. The purpose of this study was to determine how the influence quality of and perceived ease of use on online purchasing decisions mediated by consumer confidence in e-commerce application users in the city of Banda Aceh. The sampling method in this study used purposive sampling with a sample of 160 respondents. Hierarchical Linear Modeling (HLM) is used as a method of analysis to determine the effect of the analyzed variables. The results of this study indicate that the variables of Information Quality, Perceived Ease of Use and Consumer confidence have a significant effect on Online Purchasing Decisions. Furthermore, the consumer confidence variable partially mediates between the quality of information and the perceived ease of use of Online purchasing decisions.